PEMBIASAAN TADARUS AL-QUR’AN SEBELUM BELAJAR DALAM MEMBENTUK AKHLAKUL KARIMAH SISWA - Fadil, Khaidir; Supriadi, Dedi; Nurfaidah, Hilda (LPPM Institut Pendidikan Nusantara Global, 2023)
The purpose of this research is to find out the implementation, supporting and inhibiting factors of the habituation of Al-Qulr'an tadaruls before studying in forming the akhlakull karimah of class XI students at SMA Negeri 1 Leulwiliang Bogor. This type of research is a qualitative field research, the data is taken using the method of interview, observation, questionnaire and documentation. The data sources in this study are primary and secondary data sources. Checking the authenticity of the data using the triangullation technique. The analysis techniques that researchers apply are data collection, data reduction, data presentation and data verification. The results of the research indicate that the Al-Qulr'an tadaruls habituation activities are carried out every Tuesday, Thursday starting at 06.45-07.00 WIB in one day completing three Julz, Al-Qulr'an tadaruls activities round students accustomed and istiqomah reading Al-Qulr'an so that reading Al-Qulr'an is getting better. The conclusion of this research is that the habituation activity of tadaruls Al-Qulr'an has a positive impact because many students come on time, improving students' morals for the better, but there are a small number of students who come late so they do not cultivate tadaruls Al-Qulr'an. The sincere intention of students, school policy, participating stakeholders, the role of the Task Force from ROHIS members, Student Council and Class Representative Assembly (MPK) to help the Al-Qulr'an tadaruls activities become a supporting factor for Al-Qulr'an tadaruls activities in building morals. The lack of good communication, the distance between rulmah and school is an inhibiting factor.